Parents perception on pattern and effects of usage of electronic devices among school going children - Kuriakose, Roshan; N., Prasad Nayak; Saldanha, Prakash (International Journal of Contemporary Pediatrics, 2020)
Background: Over usage of electronic gadgets has a serious impact on physical activity of children leading to obesity, depression, anxiety, poor scholastic performance, strain on the eyes and triggering factor for neck and back pain (due to spondylitis).It is very important to know how to control the screen time of children by parents. Methods: Here, 75 parents were subjected to questionnaire study which contained questions on the information on usage of electronic devices among children and the adverse effects noticed. Results were analyzed using Microsoft excel software. Results: Almost all the 75 cases had access to television, 64 had access to smart phones, 24 had access to IPAD/Tablet, 8 had access to laptop and 4 had access to gaming console. It was found that 45 % were depressed / anxious when gadgets were withdrawn from them. 21 kids had no idea what to do when gadgets were not available. 54 kids had no interest in outdoor playing and 38 children were found to have decreased interaction with other family members. Conclusions: Exposure to gadgets in paediatrics population leads to poor scholastic performance, obesity, depression, decreased interaction with family and many other problems. So, it is very important to have control on child’s day to day activities and have constant vigilance on their gadget usage.